2020
DOI: 10.1108/ijssp-03-2020-0108
|View full text |Cite
|
Sign up to set email alerts
|

Popular preferences for a fully means-tested welfare provision model: social and cross-national divides in Europe

Abstract: PurposeWhether welfare provision should be broad-based or selectively targeted at the poor is one of the most common themes in social policy discourse. However, empirical evidence concerning people's preferences about these distributive justice principles is very limited. The current paper aims to bridge this gap, by analyzing Europeans' opinions about a hypothetical transformation of the welfare state that would provide social transfers and services only to people on low incomes.Design/methodology/approachThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 36 publications
1
19
1
Order By: Relevance
“…These findings seem to be in line with the central tenets of policy feedback theory, which argues that existing public policies influence the behaviors and attitudes of citizenseither in a positive, self-reinforcing way, or in a negative, selfundermining way (Campbell, 2012;Kumlin and Stadelmann-Steffen, 2014). In contrast, a more recent comparative study by Gugushvili and van Oorschot (2020) found that the extent to which a welfare state relies on means testing has no effect on individual preferences for a fully means-tested welfare provision. Yet, this study also found that country context matters: support for complete means testing was higher in countries with lower social protection spending and higher incidence of poverty, which the authors interpret as in indication of "immaturity" of the welfare state.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These findings seem to be in line with the central tenets of policy feedback theory, which argues that existing public policies influence the behaviors and attitudes of citizenseither in a positive, self-reinforcing way, or in a negative, selfundermining way (Campbell, 2012;Kumlin and Stadelmann-Steffen, 2014). In contrast, a more recent comparative study by Gugushvili and van Oorschot (2020) found that the extent to which a welfare state relies on means testing has no effect on individual preferences for a fully means-tested welfare provision. Yet, this study also found that country context matters: support for complete means testing was higher in countries with lower social protection spending and higher incidence of poverty, which the authors interpret as in indication of "immaturity" of the welfare state.…”
Section: Discussionmentioning
confidence: 82%
“…Second, our discussion clearly demonstrates that the social legitimacy of universal visa-vis selective welfare provision differs across countries (for example Gugushvili and van Oorschot, 2020), across time (for example Andersen, 2011) and across policy domains (for example Kangas, 1995). This suggests that a universally valid answer simply does not exist: it is not the case that one policy design option is more popular than the other, always and everywhere.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is often assumed that universal benefits will be most popular among (and important for) people on lower incomes. However, an analysis of the 2016 European Social Survey, covering 21 countries, reported that attitudes to the idea of completely means‐tested welfare provision were complex 12 . The analysis found that the upper and middle classes were most opposed to the idea, and that ‘more‐egalitarian people show a higher level of support for means‐testing, even though the political left has traditionally promoted universalism’.…”
Section: Introductionmentioning
confidence: 99%
“…However, an analysis of the 2016 European Social Survey, covering 21 countries, reported that attitudes to the idea of completely means‐tested welfare provision were complex. 12 The analysis found that the upper and middle classes were most opposed to the idea, and that ‘more‐egalitarian people show a higher level of support for means‐testing, even though the political left has traditionally promoted universalism’. Respondents' attitudes were also affected by the national context of different welfare state models, with people living in countries with the less generous provision and higher levels of poverty being more likely to endorse complete means testing.…”
Section: Introductionmentioning
confidence: 99%